Jinkui Shenqi Pill Combined with Pelvic Floor Biofeedback in Treatment of Postpartum Stress Urinary Incontinence with Kidney-yang Deficiency - Xueqin MIAO; Hongri WANG; Meiyun GAO; Caifeng GUO; Jifen HU; Kunmu ZHANG (康复学报)
Objective:To explore the effect and mechanism of Jinkui Shenqi pill combined with pelvic floor biofeedback in treating of postpartum stress urinary incontinence with kidney-yang deficiency.Methods:A total of 70 full-term natural labor patients diagnosed with kidney-yang deficiency stress urinary incontinence about 42 days postpartum were selected and divided into control group and treatment group by random number table, with 35 cases in each group. Control group was only treated with pelvic floor biofeedback. Treatment group was treated with pelvic floor biofeedback combined with oral Jinkui Shenqi pill. The pelvic floor muscle myoelectric potential was measured before and after treatment, the urine leakage volume in 1h urine pad test, the Short Form of International Consultation on Incontinence Questionnaire(ICI-Q-SF)scores, calculate the total effective rate and follow up the severity of stress urinary incontinence and ICI-Q-SF questionnaire scores were measured six months after treatment.Results:1) After treatment, the typeⅡmyoelectric potential, typeⅠmyoelectric potential, and typeⅠmuscle endurance potential of the two groups were higher than those before treatment, the difference was statistically significant(P<0.05), and the treatment group was higher than the control group, the difference was statistically significant(P<0.05).2)The volume of urine leakage in 1 h pad test of the two groups after treatment was less than that before treatment, the difference was statistically significant(P<0.05), and the treatment group was significantly less than the control group, the difference was statistically significant(P<0.05).3)The ICI-Q-SF questionnaire scores of the two groups after treatment were lower than those before treatment, the differences were statistically significant(P<0.05), and the treatment group was significantly lower than the control group, the difference was statistically significant(P<0.05).4) The total effective rate of the treatment group(88.60%)was higher than that of the control group(65.80%), the difference was statistically significant(P<0.05).5)Follow-up six months later, the degree of stress urinary incontinence and ICI-Q-SF questionnaire scores of the treatment group were lower than those of the control group, and the differences were statistically significant(P<0.05).Conclusion:1) Jinkui Shenqi pill combined with pelvic floor biofeedback could enhance the muscle strength of pelvic floor typeⅠand typeⅡmuscles in patients with postpartum stress urinary incontinence with kidney-yang deficiency, improve pelvic floor function recovery, reduce urine leakage, and improve patients'short-term and long-term quality of life, the treatment effect was significant and lasting, and was more effective than pure pelvic floor biofeedback therapy alone;2)The mechanism of Jinkui Shenqi pill in treating postpartum stress urinary incontinence with kidney-yang deficiency may be related to the increase of pelvic floor muscle potential.